Organizational sustainability: More a square than a triangle - Bello, Salihu, Muhammad Rayyan; Wahab, Sazali, Abd; Ida, Yasin, Md (International Journal of Business Strategy and Social Sciences, 2025)
This paper explores organizational sustainability as a comprehensive business concept by proposing an expansion of the traditional Triple Bottom Line (TBL) framework into a more inclusive Quadruple Bottom Line (QBL) model. It introduces corporate spirituality as a viable fourth pillar alongside economic, social, and environmental dimensions, emphasizing its relevance in today’s organizational practices and future societal constructs. The QBL is visually represented as a square, symbolizing equality among the four dimensions and reflecting present-day complexities and expectations. The paper serves as a preamble that conceptualizes and seeks to incubate the QBL idea, stimulating further scholarly engagement. It draws on a tailored review of existing organizational literature to justify the conceptual inclusion of corporate spirituality, positioning it as an essential component towards holistic sustainability. The theoretical foundation is rooted in Organizational Learning Theory (OLT) and Spiritual Leadership Theory (SLT), which collectively guide the paper’s argument. Accordingly, this paper emphasizes that corporate spirituality may act as an adhesive force, streamlining and strengthening the interaction between other sustainability pillars in pursuit of collective prosperity. However, as a concept paper, limitations include the absence of empirical validation and a narrow methodological scope, which necessitate future research to examine and substantiate the proposed model. Practically, the paper encourages organizational leaders and policymakers to adopt a more balanced approach to sustainability dimensions, advocating for equal attention to all organizational aspects, with corporate spirituality serving as a unifying and transformative element for businesses and society alike.